The Effectiveness of Technology Enhanced Assessment in Malaysian Higher Education for Medical Students - Sohayla M Attalla; Hana W. Jun Chen; Sakina Ruhi; Kavitha Kumar; Mahfuza Aktar; Jalal Ibrahim; Norlina Honorato; Japar Johar (Online Learning In Educational Research (OLER), 2024)
Technology-enhanced assessment (TEA) means all types of assessments that use technological aid either online or offline, either during or after learning with the objective of improving or assessing the process of learning. This study aims to assessed the effectiveness and influence of TEA on the academic performance of medical students in a Malaysian private university. A cross-sectional study was conducted and convenience sampling was applied to recruit participants. A validated online questionnaire was used and the participants were required to report their demographic characteristics, academic performance before and after using TEA, and their attitudes towards the TEA. Paired-t-test was performed to assess the difference in medical students’ mean CGPA before and after using TEA. Study findings showed that medical students have positive attitudes towards TEA and believe that TEA offers value to their learning. TEA was found to have a positive impact on the academic performance by which there is a significance difference in medical students’ mean CGPA before and after using TEA (p less than 0.05). TEA is an effective tool that can enhance the learning process among medical students. Nevertheless, the sample studied need to be more diverse to be able to generalize the results for all medical students along different universities and countries.